The Investor Psychology and Stock Market Behavior During the Initial Era of COVID-19: A Study of China, Japan, and the United States - Naseem, Sobia; Mohsin, Muhammad; Hui, Wang; Liyan, Geng; Penglai, Kun (Frontiers in Psychology, 2021)
A highly transmittable and pathogenic viral infection, COVID-19 has dramatically changed the world with a tragically large number of human lives being lost. The epidemic has brought psychological resilience and unbearable psychological pressure among patients and health professionals. The objective of this study is to analyze investor psychology and stock market behavior during COVID-19. The psychological behaviour of investors whether positive or negative toward stock market can change the picture of economy. This research explores Shanghai, Nikkei 225, and Dow Jons stock markets from 20th January 2020 to 27th April 2020 by employing Principal Component Analysis. The results showed that investor psychology was negatively related to three selected stock markets under psychological resilience and pandemic pressure. The negative emotions and pessimism urge investors to cessation financial investment in the stock market, and consequently, the stock market returns decreased. In a deadly pandemic, the masses were more concerned about their lives and livelihood and less about wealth and leisure. The finding of research contributes to the literature gap of investor psychological behavior during a pandemic outbreak. The study suggested that policymakers should design a plan to fight against COVID-19. The government should manage the health sector's budget to overcome future crises.